Active And Reactive Power Control In A Three-phase Grid-connected Pv Power System Using Dq0 Transformation - Schonardie, Mateus F.; Coelho, Roberto F.; Schmitz, Lenon; Martins, Denizar C. (Eletrônica de Potência, 2013)
This work proposes a 12 kW three-phase grid-connected single stage PWM DC-AC converter destined to process the energy provided by a photovoltaic array composed of 57 KC200GT PV modules with high power factor for any condition of solar radiation. The PWM inverter modeling and control are achieved using dq0 transformation, in order to allow the system operation also as active power filter, compensating the harmonic components and the reactive power generated by non-linear loads connected to the mains grid. An input voltage clamping technique is proposed to impose the photovoltaic operation on the maximum power point. Simulation and experimental results are presented for validating the proposed methodology.